2015
DOI: 10.1152/jn.00418.2014
|View full text |Cite
|
Sign up to set email alerts
|

Precise visuotopic organization of the blind spot representation in primate V1

Abstract: The optic disk is a region of the retina consisting mainly of ganglion cell axons and blood vessels, which generates a visual scotoma known as the blind spot (BS). Information present in the surroundings of the BS can be used to complete the missing information. However, the neuronal mechanisms underlying these perceptual phenomena are poorly understood. We investigate the topography of the BS representation (BSR) in cortical area V1 of the capuchin monkey, using single and multiple electrodes. Receptive field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
0
12
1
Order By: Relevance
“…Physiological studies have shown that a retinotopic representation of the blind spot exists as early as V1 (Awater, Kerlin, Evans, & Tong, 2005; Azzi, Gattass, Lima, Soares, & Fiorani, 2015; Fiorani, Rosa, Gattass, & Rocha-Miranda, 1992; Komatsu, Kinoshita, & Murakami, 2000, 2002; Matsumoto & Komatsu, 2005). Neurons within the blind spot representation have relatively large receptive fields that extend beyond the borders of the blind spot (Azzi et al, 2015) and can exhibit color (Komatsu et al, 2000; Komatsu et al, 2002) and orientation (Fiorani et al, 1992; Komatsu et al, 2000) selectivity. Thus one might imagine rivalry arising from competition between neurons within the blind spot representation tuned to the orthogonal orientations and conflicting colors of the bars.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies have shown that a retinotopic representation of the blind spot exists as early as V1 (Awater, Kerlin, Evans, & Tong, 2005; Azzi, Gattass, Lima, Soares, & Fiorani, 2015; Fiorani, Rosa, Gattass, & Rocha-Miranda, 1992; Komatsu, Kinoshita, & Murakami, 2000, 2002; Matsumoto & Komatsu, 2005). Neurons within the blind spot representation have relatively large receptive fields that extend beyond the borders of the blind spot (Azzi et al, 2015) and can exhibit color (Komatsu et al, 2000; Komatsu et al, 2002) and orientation (Fiorani et al, 1992; Komatsu et al, 2000) selectivity. Thus one might imagine rivalry arising from competition between neurons within the blind spot representation tuned to the orthogonal orientations and conflicting colors of the bars.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of border points uses a dot or point visual stimulus to probe the borders of the blind spot. It is the most popular strategy used in blind spot research [9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The typical method is for the observer or experimenter to move a small dot stimulus forth and back across the blind spot borders, and for the observer to report when it perceptually "disappears" (into the blind spot), and when it "appears" (from out of the blind spot).…”
Section: Detection Of Border Pointsmentioning
confidence: 99%
“…Shifts to the left or to the right (or similar shifts along other orientations) have a biological counterpart: in natural systems, specific structures (neural circuits involving long-range connections [20]) known as bipoles [21], [22] implement those shifts. Bipoles are neural circuits composed by a large number of neurons, which can together generate a weighted response that takes into account two input connection types: short-range connections (with smaller weight) and long-range connections (with larger weight).…”
Section: Dfi Detailsmentioning
confidence: 99%